A business plan for smart sensors monitoring solution for food and beverage manufacturers in Malaysia - Low, Suet Yuin (2024)
Autosens provides smart sensors monitoring solution to the food and beverage industry. The mission of Autosens is to accelerate the adoption of smart manufacturing by the food and beverage segment in Malaysia through its integrated smart sensors monitoring solution. The company focuses on providing customer centric solution through a robust customization approach and effective customer relationship management. Autosens enables F&B manufacturers to maximize their operational performance to meet their operational and business goals. Autosens does not have its own manufacturing, but sourced from various suppliers for sensors, IoT devices and software to create its smart sensors system. It has a core product sensors BrandB and a key brand of open platform IoT enabled software.